Lithuanian Neologisms: the Aspect of Sex Expression - Murmulaitytė, Daiva (Lietuvių kalba, 2021)
The article discusses the nouns with the (potential) seme of sex in “The Database of Lithuanian Neologisms“ in terms of their origin, word formation, semantics and usage. The majority of names of animated beings (people, animals as well as phantasy creatures, personified phenomena, etc.) are motion nouns (substantiva mobilia), while the others are of masculine, feminine or neutral gender. New coinages (separate, occasional as well as usual ones) show that more means of naming objects according to their sex differences are used in modern Lithuanian language compared to the ones provided for in Lithuanian language grammars or descriptors of word formation, which were written long time ago. Moreover, usual derivational affixes expand their semantics. For example, the suffix -inas is used not only in new coinages to name males (beždžioninas ‘a monkey male’, žirafinas ‘a giraffe male’), but also to coin names for certain men (barakudinas ‘a predatory man, who seeks profit from rich women’ ← barakuda ‘a young, determined and selfish woman, seducing stranger rich men’, žvaigždinas ‘a star – celebrity of masculine gender’ ← žvaigždė ‘a famous woman, celebrity’). The inflection -ė is broadly used not only for new names of female animals, but also to name women (krivė ‘a female priest in the Baltic religion’, šviesulė ‘a famous (usually in the entertainment world) woman’, urėdė ‘a woman in the position of forest manager’, etc.). Changing social relations as well as changing attitudes towards non-heterosexual persons, the same-sex marriages, louder-sounding ideas of feminism, levelling of female and male occupations, activities and hobbies, etc., call for coinages that are needed to name new realities. And sometimes it is necessary not to find a name for a new reality, but to emphasise or, less frequently, to level the gender of already named reality. For this reason, such new words were coined: tėvė ‘according to the ideology of genderism – one of the members of family growing children (regardless of gender)’, kareivė ‘a woman performing military conscription’, kavalierė ‘a woman, who was awarded the order’; slaugas ‘a male nurse’, sesutis ‘a man working as a nurse’, auklius ‘a man working as a nanny’, mūzas ‘a masculine form of the noun mūza (a goddess, a female inspirer of poetic creation’; žmoga ‘a feminist name for a woman or a person detached from the gender’, and others. Some of them naturally became part of the standard Lithuanian, other words remained occasional. The article raises the question whether/how dictionaries should present potential (i.e., foreseen by the system, but practically not attested) words (forms). On the basis of examples of new motion nouns (new coinages), there emerge considerations how to perceive nouns, which have the same lexical stem and paradigms of two (male and female) genders – as separate words or different forms of the same words? The answer to this question may define how substantiva mobilia could/should be presented in the dictionaries in a more systematic way.